Implementasi Program Open Defecation Free (ODF) untuk Kesehatan Masyarakat - Rida Diana; Yusuf Adam Hilman; Bambang Widiyahseno; Robby Darwis Nasution (Wacana Publik, 2022)
This research was conducted to describe how the government's strategy aims to describe how the local government's strategy is related to the implementation of the Open Defecation Free (ODF) program in Sambilawang Village, Bungkal District, Ponorogo. some factors that emerged were also examined in this study such as supporting factors that became positive assets, as well as inhibiting factors that weakened the program implementation process. This type of research is descriptive research that aims to describe what has existed and is valid. Basically, this research is of a descriptive type which puts forward explanations in the form of a series of logical, systematic sentences, and is built on the findings of facts in the field. The results of this research reveal that the strategy of the Ponorogo local government in implementing the ODF program has so far been at an optimal level, effective and meets a good scale. In particular, Sambilawang Village, which has been given a focus on how to socialize and build decent latrines evenly among the society. Commitment and cooperative action from the Sambilawang Village Government and Pemdes and other village communities in the success of the ODF program is marked by the award at the provincial level which states that Ponorogo is free of ODF or that the quality of the environment is in the livable category. However, the fact that Ponorogo is free from ODF does not necessarily fully evaluate the level of public awareness regarding the findings of open defecation even though they already have proper latrines in their respective homes. But, the fact that Ponorogo is free from ODF does not necessarily fully evaluate the level of public awareness regarding the findings of open defecation even though they already have proper latrines in their respective homes.